ComparaciÃ³n de la Dosis Absorbida Determinada por DosimetrÃa Directa con los ParÃ¡metros del TomÃ³grafo Computarizado del HPGDR - Vilema, Erika Magaly Tierra; Morocho, Blanca Fabiola Pumalema; Saavedra, Myrian Cecilia Borja; Cevallos, William Bladimir Cevallos; Lucero, Marina Leonor Bonilla (European Scientific Journal, ESJ, 2019)
This paper focuses on comparing the relationship between the dose of radiation obtained from the dosimeter with the dosimetric quantities of the equipment in single skull tomography in the Provincial General Regional Hospital Riobamba, during the period from February to April 2018. The scan was carried out using the Toshiba TSX-031A 16-helical slice tomograph and a DoseRAE2 direct-reading electronic dosimeter. This was placed 3 centimeters from the patient’s nape, and the delivered dose was controlled by the operator’s console monitor. The research was conducted with 48 adult patients with an age range of 18 to 60 years. The data was analyzed using RStudio and Microsoft Excel. The Kolmogorov Smirnov test and the Student t test were applied. The results indicated that the average values of the tomograph have an emission of excessive radiation of 0.59 mSv over the reference value according to the European Community and the American College of Radiology; knowing thus the dose to which the patient is irradiated. It is recommended to calibrate the dosimetric parameters of the equipment to avoid an overdose and the biological effects on the patient. El objetivo de la investigaciÃ³n fue comparar la relaciÃ³n existente entre la dosis de radiaciÃ³n obtenida del dosÃmetro, con las cantidades dosimÃ©tricas del equipo en tomografÃas de crÃ¡neo simple en el Hospital Provincial Regional General Docente Riobamba, durante el perÃodo de febrero a abril del 2018. Para la exploraciÃ³n se utilizÃ³ el tomÃ³grafo Toshiba TSX-031A de 16 cortes helicoidal y un dosÃmetro electrÃ³nico de lectura directa DoseRAE2, a 3 centÃmetros de la nuca del paciente y se controlÃ³ la dosis suministrada mediante el monitor de consola del operador. La investigaciÃ³n se realizÃ³ con 48 pacientes adultos con un intervalo de edad de 18 a 60 aÃ±os. Los datos fueron analizados mediante R-Studio y Microsoft Excel. Se aplicÃ³ el test de Kolmogorov Smirnov y la prueba de t de Student. Los resultados indicaron que los valores medios del tomÃ³grafo tienen una emisiÃ³n de radiaciÃ³n excesiva de 0,59 mSv sobre el valor de referencia segÃºn la Comunidad Europea y el Colegio Americano de RadiologÃa; conociendo asÃ la dosis a la cual se irradia al paciente. Se recomienda la calibraciÃ³n de los parÃ¡metros dosimÃ©tricos del equipo para evitar una sobredosis y los efectos biolÃ³gicos en el paciente.